2018
DOI: 10.24200/ijpb.2018.58150
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Attachment and Subjective Well-being: The Mediating Role of Emotion Regulation Skill

Abstract: Attachment styles are considered important not only for adults' close relationships but also for individual's well-being, reflecting the subjective quality of life, covering positive mood, vitality, and interest in things. Emotion regulation is considered to be in direct relation with these variables and expected to play a mediating role in the association between attachment and well-being. The aim of this study was to obtain better insight into the associations between attachment styles and subjective well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…16,17 This excessive anxiety and neediness may cause them to become insecure and overly dependent in intimate relationships, which can reduce the individual's subjective well-being. 18 Moreover, their anxiety levels may increase due to persistent worry. 19 On the other hand, individuals with insecure attachments usually tend to remain independent and avoid emotional connections.…”
Section: Subjective Well-being As a Mediatormentioning
confidence: 99%
“…16,17 This excessive anxiety and neediness may cause them to become insecure and overly dependent in intimate relationships, which can reduce the individual's subjective well-being. 18 Moreover, their anxiety levels may increase due to persistent worry. 19 On the other hand, individuals with insecure attachments usually tend to remain independent and avoid emotional connections.…”
Section: Subjective Well-being As a Mediatormentioning
confidence: 99%
“…The insecure attachment lowers the flexibility to tackle stressful life events and influences a person to break down psychologically in crisis moments. Insecure attachment can therefore be observed as a general weakness to mental disorders, with the specificity of genetics, developmental, and environmental factors 19 .…”
Section: Attachment Styles and Psychological Wellbeingmentioning
confidence: 99%
“…Regarding the bond between psychological well-being and type of attachment, some studies have discovered that the attachment styles of individuals play a significant role in influencing well-being [ 20 , 31 , 41 , 44 ]. According to these findings, insecure attachment styles (such as anxious and avoidant attachment) are inversely associated with overall well-being, whereas attachment security is positively correlated [ 7 , 41 , 42 , 44 , 45 ]. Specifically, people who had secure attachment experiences displayed good interpersonal relationships, high degrees of autonomy, adequate environmental mastery, a sense of purpose in life, and high levels of self-acceptance [ 46 ]; in addition, high levels of autonomy, personal growth (in terms of competence), and positive relationships with others are related to the secure attachment of an individual [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, those who expressed avoidant attachment had trouble managing their interactions with others and their surroundings, and they also indicated less self-acceptance than the other groups. The mediational roles of dispositional mindfulness, psychological inflexibility, and resilience in the relationship between attachment styles and psychological well-being were examined in the Italian context by Calvo et al [ 45 ]. The data suggested that lower levels of psychological well-being were correlated with higher levels of attachment anxiety and avoidance.…”
Section: Introductionmentioning
confidence: 99%